IN VITRO ANTI-PROLIFERATIVE EFFECT OF ANNONA SQUAMOSA (L.) LEAF IN THE REGULATION OF APOPTOTIC GENES IN HEPG2 CELL LINE - V. VANITHA; K. J. UMA DEVI; K. VIJAYALAKSHMI (International Journal of Pharma and Bio Sciences, 2016)
The plant, Annona squamosa traditionally known as custard apple possesses potent bioactive principles in all its parts. The effect of ethyl acetate fraction of ethanolic leaf extract of Annona squamosa (EAELAS) was studied on a HepG2 cell line. The role of phytonutrients present in the active ethyl acetate fraction of the ethanolic leaf Annona squamosa in regulating the balance between cell proliferation and apoptosis via modulating the expression pattern of proliferation and apoptosis regulating genes in HepG2 cell line was analyzed by studying the mRNA levels of two genes Bcl2, and P53 involved in apoptotic pathway. The EAELAS caused significant apoptotic tumor cell death with enhanced Caspase 3 activity, down regulation of antiapoptotic gene Bcl-2. In this study, apoptosis was upregulated by p53 and caspase 3 expressions and simultaneously down regulating the Bcl2. Thus, the extract increased nuclear condensation and DNA fragmentation and the ability of the active fraction from Annona squamosa was potent to induce apoptosis by a cascade of events suggests that it might be an ideal therapeutic for many solid tumors of the liver.